Letter - Thompson, J.
028-0075-001 CABLE CODES:- A.B.C 6th EDITION WESTERN UNION 5 LETTER BENTLEY COMPLETE PHRASE BENTLEY SECOND PHRASE and PRIVATE CO-OPERATIVE WHOLESALE SOCIETY Ltd. Exporters, Buying and Shipping Agents. Export Department. 1, Balloon Street. Manchester, 4. IMPORTANT PLEASE ADDRESS CORRES INVOICES ETC EXPORT REF: 6422.ST/MM. TELEGRAPHIC ADDRESS: "WHOLESALE, MANCHESTER" TELEPHONE NO.: BLACKFRIARS 1212. 25th January, 1937. Phoned 26th Jan. Sugar Bill of Lading coming later. They will amend cover note from "Liverpool" to "London." Mr. Tewson, The National Council of Labour, Transport House, Smith Square, LONDON. S.W.1. Dear Sir, We have pleasure in attaching hereto copy Bill of Lading, Insurance Cover Note and invoices in respect of goods shipped per s.s. CARPIO from London to Valencia on your behalf, which you will doubtless find in order. As previously arranged, the original Bill of Lading has gone forward by carrying steamer to Senor Carlos Hernandez, U.G.T. Salvador Sequi 5, Valencia, and we will deliver the second original Bill of Lading to you immediately same reaches us from the steamship company, probably to-morrow. Shipment of the balance of your order is, of course, being effected by s.s. PELAYO, which vessel we understand will leave Liverpool for Valencia to-morrow. Copy Bill of Lading and invoices covering this shipment will, therefore, follow about Wednesday. Meanwhile, we trust that you will find everything to your entire satisfaction in so far as the first portion of your order is concerned, and remain, Yours faithfully, J. Thompson, Export Department. 292/946/28/75